NiCo2O4 / MnO2 composite nanomaterial as well as preparation method and application thereof
The preparation of NiCo2O4/MnO2 composite nanomaterials through electrodeposition and in-situ deposition solves the problems of low electrode specific capacity and narrow charge and discharge voltage window of a single NiCo2O4 material, which significantly improves the power density, energy density and cycling stability of the electrode.
Patent Information
- Application Number
- CN202411398426.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-25
AI Technical Summary
The electrodes with a single NiCo2O4 material have a lower specific capacity and a narrow charge and discharge voltage window.
NiCo2O4/MnO2 composite nanomaterials were prepared by combining electrodeposition and in-situ deposition, introducing MnO2 with porous, high conductivity, high specific capacitance and high ion transport efficiency.
The power density, energy density and cyclic stability of composite nanostructured electrodes are greatly improved, and the specific capacity and charge and discharge voltage window of the electrode material are improved.
Smart Images

Figure CN119517627A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a NiCo2O4 / MnO2 composite nanomaterial and a preparation method and application thereof. Background Art
[0002] Supercapacitor refers to a new type of energy storage device between traditional capacitors and rechargeable batteries. It has the characteristics of fast charging and discharging of capacitors and the energy storage characteristics of batteries. There are two main reactions that occur during the charging / discharging process of supercapacitors. One is the physical reaction process of double-layer charging and discharging, and the other is a fast and reversible electrochemical reaction process that occurs on the electrode surface. Compared with batteries and traditional physical capacitors, supercapacitors have the advantages of high power density (102~104kW / kg), long cycle life, wide operating temperature range (40~65℃), and green environmental protection.
[0003] Supercapacitors can be divided into double-layer supercapacitors and pseudocapacitors according to their mechanism. Double-layer supercapacitor electrode materials mainly include carbon material electrode materials such as nanocarbon fibers, carbon aerogels, and carbon nanotubes; pseudocapacitor supercapacitor electrode materials mainly include metal oxide electrode materials such as nickel oxide, manganese oxide, and cobalt oxide, as well as conductive polymer electrode materials such as polyaniline, polythiophene, and polypyrrole. Binary metal oxide electrode materials, such as NiCo2O4, have significant specific capacitance (SC) and energy density, and have attracted much attention from researchers. They are one of the potential materials for high-performance electrochemical energy storage electrodes. However, the single NiCo2O4 material electrode has a low specific capacity and a narrow charge and discharge voltage window. Summary of the invention
[0004] Based on this, in order to solve the technical problems that the current single NiCo2O4 material electrode has low specific capacity and a narrow charge and discharge voltage window, the present invention provides a NiCo2O4 / MnO2 composite nanomaterial and its preparation method and application.
[0005] The first object of the present invention is to provide a method for preparing a NiCo2O4 / MnO2 composite nanomaterial, which comprises the following steps:
[0006] S1. In a three-electrode system with nickel foam as the working electrode, a solution prepared by dissolving a cobalt source and a nickel source in deionized water is used as an electrolyte to carry out electrodeposition, and the nickel foam is taken out, washed and dried to obtain a nickel-cobalt double hydroxide precursor;
[0007] S2. After sintering the nickel-cobalt double hydroxide precursor, NiCo2O4 nanosheets are obtained;
[0008] S3. In an ice water bath, potassium permanganate and manganese sulfate are dispersed in deionized water to obtain a mixed solution, the NiCo2O4 nanosheets are placed in the mixed solution, stirred and then allowed to stand at room temperature, and dried to obtain a NiCo2O4 / MnO2 composite nanomaterial.
[0009] The present invention prepares NiCo2O4 / MnO2 composite nano metal oxide supercapacitor electrode material by combining electrodeposition and in-situ deposition, introduces porous, highly conductive, high specific capacitance and high ion transport efficiency MnO2 into the electrode material, thereby greatly improving the power density, energy density and cycle stability of the composite nanostructured electrode, and the obtained electrode material has high specific capacity and a large charge and discharge voltage window.
[0010] As a further improvement of the above solution of the present invention, in step S1, the voltage of the electrodeposition is -0.5 to -1.2 V, and the time of the electrodeposition is 1 to 30 minutes.
[0011] As a further improvement of the above solution of the present invention, in step S1, the three-electrode system uses a platinum sheet as a counter electrode and saturated calomel as a reference electrode;
[0012] And / or, the nickel foam is pretreated nickel foam, and the pretreatment method is: in an ultrasonic bath, washing the nickel foam with a 0.5-3M HCl hydrochloric acid solution for 3-5 minutes, and then ultrasonically washing with deionized water and anhydrous ethanol for 3-5 minutes respectively.
[0013] As a further improvement of the above scheme of the present invention, in step S1, the cobalt source is Co(NO3)2·6H2O, the nickel source is Ni(NO3)2·6H2O, the concentration of Co(NO3)2·6H2O in the electrolyte is 4-6mM, and the concentration of Ni(NO3)2·6H2O is 2-3mM.
[0014] As a further improvement of the above scheme of the present invention, in step S1, the cleaning is to rinse the surface of the nickel foam with deionized water and alcohol in sequence, and the drying is to dry it in a drying oven at 60° C. to 80° C. for 10 to 16 hours.
[0015] As a further improvement of the above solution of the present invention, in step S2, the sintering is carried out in a tubular sintering furnace in an air atmosphere at 250-450° C. for 1-3 hours.
[0016] As a further improvement of the above solution of the present invention, in step S2, the heating rate of the sintering is 1-10°C / min.
[0017] As a further improvement of the above scheme of the present invention, in step S3, the molar ratio of potassium permanganate to manganese sulfate is 1-2:2-1;
[0018] And / or, in step S3, the drying is carried out in a drying oven at 60° C. to 80° C. for 10 to 16 hours.
[0019] The second object of the present invention is to provide a NiCo2O4 / MnO2 composite nanomaterial, which is prepared by the method for preparing the NiCo2O4 / MnO2 composite nanomaterial as described above.
[0020] The third object of the present invention is to provide a use of the NiCo2O4 / MnO2 composite nanomaterial as described above as a supercapacitor electrode material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention prepares NiCo2O4 / MnO2 composite nano metal oxide supercapacitor electrode material by combining electrodeposition and in-situ deposition, introduces porous, highly conductive, high specific capacitance and high ion transport efficiency MnO2 into the electrode material, thereby greatly improving the power density, energy density and cycle stability of the composite nanostructured electrode, and the obtained electrode material has high specific capacity and a large charge and discharge voltage window. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The electron microscope photograph of the NiCo2O4 / MnO2 composite nanomaterial prepared in Examples 1-3 of the present invention;
[0024] Figure 2 The cycle performance diagram of the NiCo2O4 / MnO2 composite nanomaterial prepared in Examples 1-3 of the present invention;
[0025] Figure 3 The charge and discharge diagram of the NiCo2O4 / MnO2 composite nanomaterial prepared in Examples 1-3 of the present invention;
[0026] Figure 4 This is a current density-to-capacitance curve of the NiCo2O4 / MnO2 composite nanomaterials prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0027] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0029] Example 1
[0030] This embodiment provides a NiCo2O4 / MnO2 composite nanomaterial, the preparation method of which includes the following steps:
[0031] S1. Wash the nickel foam with 1M HCl solution in an ultrasonic bath for 5 min to remove NiO on the surface. x layer, and then ultrasonically cleaned with deionized water and anhydrous ethanol for 3 minutes respectively, cut the nickel foam into about 2cm×2cm, and use the nickel foam as the working electrode, the platinum sheet as the counter electrode, and the saturated calomel as the reference electrode to form a three-electrode system. The electrolyte is an electrolyte containing 4mM Co(NO3)2·6H2O and 2mM Ni(NO3)2·6H2O. Use an electrochemical workstation to electrodeposit at -1.0V for 5min at different temperatures; take out the nickel foam and rinse the suspended matter on the surface of the nickel foam with deionized water and alcohol in turn, and then dry the nickel foam in a drying oven at 60℃ for 12h to obtain a nickel-cobalt double hydroxide precursor.
[0032] S2. The nickel-cobalt double hydroxide precursor is placed in a tubular sintering furnace, heated to 300° C. at a rate of 1° C. / min in air and continuously calcined at 300° C. for 2 hours to obtain NiCo2O4 nanosheets.
[0033] S3. In an ice water bath, potassium permanganate and manganese sulfate in a molar ratio of 1:2 were dispersed in 50 ml of deionized water to obtain a mixed solution. NiCo2O4 nanosheets were placed in the mixed solution and stirred for 10 min. The mixture was then allowed to stand at room temperature and then dried in a drying oven at 60°C for 12 h to obtain NiCo2O4 / MnO2 composite nanomaterials.
[0034] Example 2
[0035] This embodiment provides a NiCo2O4 / MnO2 composite nanomaterial, the preparation method of which includes the following steps:
[0036] S1. Wash the nickel foam with 1M HCl solution in an ultrasonic bath for 5 min to remove NiO on the surface. xlayer, and then ultrasonically cleaned with deionized water and anhydrous ethanol for 3 minutes respectively, cut the nickel foam into about 2cm×2cm, and use the nickel foam as the working electrode, the platinum sheet as the counter electrode, and the saturated calomel as the reference electrode to form a three-electrode system. The electrolyte is an electrolyte containing 4mM Co(NO3)2·6H2O and 2mM Ni(NO3)2·6H2O. Use an electrochemical workstation to electrodeposit at -1.0V for 5min at different temperatures; take out the nickel foam and rinse the suspended matter on the surface of the nickel foam with deionized water and alcohol in turn, and then dry the nickel foam in a drying oven at 60℃ for 12h to obtain a nickel-cobalt double hydroxide precursor.
[0037] S2. The nickel-cobalt double hydroxide precursor is placed in a tubular sintering furnace, heated to 300° C. at a rate of 1° C. / min in air and continuously calcined at 300° C. for 2 hours to obtain NiCo2O4 nanosheets.
[0038] S3. In an ice water bath, potassium permanganate and manganese sulfate in a molar ratio of 1:2 were dispersed in 50 ml of deionized water to obtain a mixed solution. NiCo2O4 nanosheets were placed in the mixed solution and stirred for 30 min. The mixture was then allowed to stand at room temperature and then dried in a drying oven at 60°C for 12 h to obtain NiCo2O4 / MnO2 composite nanomaterials.
[0039] Example 3
[0040] This embodiment provides a NiCo2O4 / MnO2 composite nanomaterial, the preparation method of which includes the following steps:
[0041] S1. Wash the nickel foam with 1M HCl solution in an ultrasonic bath for 5 min to remove NiO on the surface. x layer, and then ultrasonically cleaned with deionized water and anhydrous ethanol for 3 minutes respectively, cut the nickel foam into about 2cm×2cm, and use the nickel foam as the working electrode, the platinum sheet as the counter electrode, and the saturated calomel as the reference electrode to form a three-electrode system. The electrolyte is an electrolyte containing 4mM Co(NO3)2·6H2O and 2mM Ni(NO3)2·6H2O. Use an electrochemical workstation to electrodeposit at -1.0V for 5min at different temperatures; take out the nickel foam and rinse the suspended matter on the surface of the nickel foam with deionized water and alcohol in turn, and then dry the nickel foam in a drying oven at 60℃ for 12h to obtain a nickel-cobalt double hydroxide precursor.
[0042] S2. The nickel-cobalt double hydroxide precursor is placed in a tubular sintering furnace, heated to 300° C. at a rate of 1° C. / min in air and continuously calcined at 300° C. for 2 hours to obtain NiCo2O4 nanosheets.
[0043] S3. In an ice water bath, potassium permanganate and manganese sulfate in a molar ratio of 1:2 were dispersed in 50 ml of deionized water to obtain a mixed solution. NiCo2O4 nanosheets were placed in the mixed solution and stirred for 60 min. The mixture was then allowed to stand at room temperature and then dried in a drying oven at 60°C for 12 h to obtain NiCo2O4 / MnO2 composite nanomaterials.
[0044] Figure 1 The electron microscope photograph of the NiCo2O4 / MnO2 composite nanomaterial prepared in Examples 1-3, wherein: Figure 1 (a) and Figure 1 (d) is an electron microscope photograph of the NiCo2O4 / MnO2 composite nanomaterial obtained in Example 1. Figure 1 (b) and Figure 1 (e) is an electron microscope photograph of the NiCo2O4 / MnO2 composite nanomaterial obtained in Example 2. Figure 1 (c) and Figure 1 (f) is an electron microscope photograph of the NiCo2O4 / MnO2 composite nanomaterial obtained in Example 3; Figure 1 It can be seen that the large granular nanostructures grow evenly on the surface of the nickel foam and are interconnected, which is beneficial to improving the mechanical stability of the electrode material; the high-magnification SEM image shows that the surface of the NiCo2O4 / MnO2 nanostructure is smooth, indicating that the sample treated with high-temperature annealing is highly crystallized; the NiCo2O4 / MnO2 nanosheets obtained at different times are significantly different. It can be seen that the nanosheets obtained when the in-situ deposition time of MnO2 is 30 minutes are larger and the three-dimensional network structure is clearer and more obvious, such as Figure 1 (b) and Figure 1 (e), while at other times the nanosheets are small and irregular, which is not conducive to the transfer of electrons.
[0045] Test Case
[0046] The composite nanomaterials prepared in the above Examples 1-3 were subjected to the following performance tests:
[0047] (1) Cycle performance
[0048] Cyclic voltammetry test, the principle of cyclic voltammetry (CV) is to apply a scanning voltage to the reference electrode and the working electrode to obtain a relationship curve between the current and the potential. The reaction mechanism of the electrode can be judged based on the waveform, peak potential and current value obtained by scanning. As the scanning rate increases, the peak current increases, the closed CV curve area also increases, and the corresponding specific capacity is higher. The instrument used in this test example is the CHI660D electrochemical workstation.
[0049] Figure 2The cyclic voltammetry (CV) curve of the NiCo2O4 / MnO2 composite nanomaterials prepared in Examples 1-3 of the present invention in the voltage range of 0.1-0.6V is shown in FIG. Figure 2 It can be seen that the CV curves of the NiCo2O4 / MnO2 electrode have obvious redox peaks. With the increase of the scan rate, the reduction peak and oxidation peak shift to the positive and negative directions of the voltage respectively. The electrode materials of NiCo2O4 / MnO2 with different MnO2 deposition times have different redox peaks at 20mV·s -1 It was found that the peak current density was the highest when MnO2 was in-situ deposited for 30 minutes, indicating that the in-situ growth for 30 minutes has excellent specific capacitance performance compared with other growth times.
[0050] (2) Constant current charge and discharge test
[0051] The Galvanostatic Charge-Discharge (GCD) test uses a constant current to test the specific capacity and rate performance of the electrode material. The main principle is to charge and discharge the electrode under constant current and observe the voltage change curve. This test example uses a CHI660D electrochemical workstation.
[0052] Figure 3 The charge and discharge diagram of the NiCo2O4 / MnO2 composite nanomaterial prepared in Examples 1-3 of the present invention is shown in FIG. Figure 3 It can be seen that each GCD curve has an obvious voltage platform. The electrode materials of NiCo2O4 / MnO2 with different MnO2 deposition times have a significant voltage platform at a current density of 1 A·g -1 When GCD test was performed, it was found that the charge and discharge time was the longest and the capacity was the highest when MnO2 was grown in situ for 30 minutes, which proved that when the MnO2 deposition time was 30 minutes, the NiCo2O4 / MnO2 composite electrode material had the best specific capacity performance.
[0053] (3) Calculation of electrochemical performance
[0054] The specific capacitance is mainly calculated based on the CV and GCD curves, such as formula (2-1):
[0055]
[0056] The unit of specific capacity is F·g -1 , I represents the current during the charge and discharge process, t represents the time taken for discharge, m represents the amount of active substances in the test electrode material, and V represents the charge and discharge voltage.
[0057] Figure 41 is a current density specific capacitance value curve of the NiCo2O4@MnO2 composite nanomaterials prepared in Examples 1-3 of the present invention, and Table 1 is the specific capacitance value of the NiCo2O4@MnO2 composite nanomaterials prepared in Examples 1-3 of the present invention at a current density of 1A / g. Figure 4 As can be seen from Table 1, the composite nanomaterial prepared in Example 2 (chemical deposition for 30 min) has the highest specific capacitance value at current density.
[0058] Table 1
[0059]
[0060] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0061] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a NiCo2O4 / MnO2 composite nanomaterial, characterized in that: It includes the following steps: S1. In a three-electrode system with nickel foam as the working electrode, a solution prepared by dissolving a cobalt source and a nickel source in deionized water is used as an electrolyte to carry out electrodeposition, and the nickel foam is taken out, washed and dried to obtain a nickel-cobalt double hydroxide precursor; S2. After sintering the nickel-cobalt double hydroxide precursor, NiCo2O4 nanosheets are obtained; S3. In an ice water bath, potassium permanganate and manganese sulfate are dispersed in deionized water to obtain a mixed solution, and the NiCo2O4 nanosheets are placed in the mixed solution, stirred, and then allowed to stand at room temperature. After drying, NiCo2O4 nanosheets are obtained. 4 / MnO2 composite nanomaterials.
2. The method for preparing the NiCo2O4 / MnO2 composite nanomaterial according to claim 1, characterized in that: In step S1, the voltage of the electrodeposition is -0.5 to -1.2 V, and the time of the electrodeposition is 1 to 30 minutes.
3. The method for preparing the NiCo2O4 / MnO2 composite nanomaterial according to claim 1, characterized in that: In step S1, the three-electrode system uses a platinum sheet as a counter electrode and saturated calomel as a reference electrode; And / or, the nickel foam is pretreated nickel foam, and the pretreatment method is: in an ultrasonic bath, washing the nickel foam with a 0.5-3M HCl hydrochloric acid solution for 3 to 5 minutes, and then ultrasonically washing with deionized water and anhydrous ethanol for 3 to 5 minutes respectively.
4. The method for preparing the NiCo2O4 / MnO2 composite nanomaterial according to claim 1, characterized in that: In step S1, the cobalt source is Co(NO3)2·6H2O, the nickel source is Ni(NO3)2·6H2O, the concentration of Co(NO3)2·6H2O in the electrolyte is 4-6mM, and the concentration of Ni(NO3)2·6H2O is 2-3mM.
5. The method for preparing the NiCo2O4 / MnO2 composite nanomaterial according to claim 1, characterized in that: In step S1, the cleaning is to rinse the surface of the nickel foam with deionized water and alcohol in sequence, and the drying is to dry it in a drying oven at 60° C. to 80° C. for 10 to 16 hours.
6. The method for preparing the NiCo2O4 / MnO2 composite nanomaterial according to claim 1, characterized in that: In step S2, the sintering is carried out in a tubular sintering furnace in an air atmosphere at 250-450°C for 1-3 hours.
7. The method for preparing the NiCo2O4 / MnO2 composite nanomaterial according to claim 1, characterized in that: In step S2, the heating rate of the sintering is 1-10°C / min.
8. The method for preparing the NiCo2O4 / MnO2 composite nanomaterial according to claim 1, characterized in that: In step S3, the molar ratio of potassium permanganate to manganese sulfate is 1-2:2-1; And / or, in step S3, the drying is carried out in a drying oven at 60° C. to 80° C. for 10 to 16 hours.
9. A NiCo2O4 / MnO2 composite nanomaterial, characterized in that: The composite nanomaterial is prepared by the method for preparing the NiCo2O4 / MnO2 composite nanomaterial as described in any one of claims 1 to 8.
10. Use of the NiCo2O4 / MnO2 composite nanomaterial as claimed in claim 9 as a supercapacitor electrode material.